2020
DOI: 10.35196/rfm.2020.2.181
|View full text |Cite
|
Sign up to set email alerts
|

Indicadores De Productividad Y Calidad De Gel De Sábila en Condiciones De Estrés Salino

Abstract: Las zonas áridas abarcan grandes regiones de México con problemas de escasez hídrica, suelos superficiales, pobres en materia orgánica y altos contenidos de sales. La sábila [Aloe vera (L.) Burm. f.] es una alternativa viable de producción ante condiciones ambientales limitantes. El objetivo de este estudio fue evaluar el efecto de la salinidad en el crecimiento de las hojas y calidad de gel de la sábila. El estudio consistió en probar seis tratamientos salinos: 0, 500, 1000, 2000, 4000 y 8000 mg L-1 de NaCl, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…The greatest soluble solids and precipitable solids in methanol, at the lowest irrigation treatment, represent an alternative management strategy for obtaining the commercial standards established by the International Aloe Science Council (IASC) (2008). These two gel quality components were also improved in aloe plants exposed to saline stress (Sifuentes-Rodríguez et al, 2020).…”
Section: Some Gel Quality Indicatorsmentioning
confidence: 88%
See 1 more Smart Citation
“…The greatest soluble solids and precipitable solids in methanol, at the lowest irrigation treatment, represent an alternative management strategy for obtaining the commercial standards established by the International Aloe Science Council (IASC) (2008). These two gel quality components were also improved in aloe plants exposed to saline stress (Sifuentes-Rodríguez et al, 2020).…”
Section: Some Gel Quality Indicatorsmentioning
confidence: 88%
“…Regardless of aloe plant reduction, the gel quality enhancement found in the 42% FC irrigation treatment, has an important commercial impact on the aloe plant industry. For instance, high ash content in the plant tissues indicates high concentrations of mineral nutrients (K, Ca, Mg, Ca, and others) desired by the industry (Sifuentes-Rodríguez et al, 2020;Cabrera-Suárez et al, 2012). Similarly, the pH values reported in this study are similar to those found in gels used as raw material for making different industrial products (Choi and Chung, 2003).…”
Section: Some Gel Quality Indicatorsmentioning
confidence: 99%
“…These results matched with other studies where an increase of TS concentration in A. vera gel was obtained by an increase in soil salinity. According to Sifuentes- Rodríguez et al (2020), the concentration of sugars and percentage of total soluble solids was the highest as so did the soil salinity, even when aloe leaf production was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…So, it is a productive alternative for marginal areas where traditional crops are no longer economically competitive (Davis et al 2019). In addition, aloe leaves products, such as gel, juice as well as powdery are in high demand in the international market due to multiple benefits in the food, medical, and cosmetic industries (Sifuentes- Rodríguez et al 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation